Systematic review and meta-analysis of the relationship between foreign language anxiety and academic achievement in Chinese language learners - Wenjing Chen (Frontiers in Education)
Foreign language anxiety significantly affects academic performance, particularly in Chinese language learning. This study aims to meta-analyze the relationship between foreign language anxiety and academic performance among individuals learning Chinese as a second language. A meta-analytic approach was employed, analyzing studies involving 3,633 Chinese language learners and 59 independent effect sizes. The degree of correlation between foreign language anxiety and academic performance was examined, along with potential moderating variables. A moderate negative correlation (r = −0.33) was found between foreign language anxiety and academic performance. Subgroup analysis and meta-regression revealed that age, gender (biological sex), and the type of “anxiety–performance” relationship were moderating variables in this relationship. The findings suggest that (1) anxiety related to writing and listening in Chinese significantly negatively impacts language performance; (2) male learners and older learners are more susceptible to the influence of anxiety on their Chinese learning outcomes; and (3) the negative correlations between reading anxiety and reading performance, as well as listening anxiety and listening performance, are most pronounced. These results imply that educators should help learners recognize and manage anxiety, utilize AI technologies to create supportive learning environments, and foster positive emotional states to mitigate the negative effects of anxiety.